[BP.08.02] THE ROLE OF SIRT3 MEDIATED ENDOTHELIAL TO MESENCHYMAL TRANSITION IN HYPERTENSIVE RENAL FIBROSIS. (September 2017) - Lin, J.; Shen, W.; Wei, T.; Gao, P.
Abstract : Objective: While the transition of epithelial cells into myofibroblasts has been intensively investigated in renal fibrosis, endothelial to mesenchymal transition (EndoMT) has recently emerged as another potentially important mechanism in promoting fibrosis in chronic kidney disease. However, its underlying molecular mechanisms remain to be elucidated. Design and method: Adult male wild-type (WT), SIRT3 knockout (KO) and SIRT3 endothelial cell-specific transgenic (EC-Tg) mice were infused with Angiotensin II (Ang II, 1000ng/kg/min) for 4 weeks. Body weight, blood pressure, renal function, EndoMT, renal capillary density and expression of SIRT3 were assessed. In addition, cultured mouse glomerular endothelial cells (MGECs) were treated with Ang II, and endothelial function and involved SIRT3 signaling pathway were evaluated 72 h later. Results: Ang II resulted in a significant reduction of SIRT3 expression, induction of EndoMT, and fibrosis in the kidney. SIRT3 KO mice subjected to Ang II infusion exhibited more severe renal dysfunction and increase of EndoMT markers than that of wild type mice. Importantly, SIRT3 EC-Tg mice ameliorated Ang II induced renal fibrosis and EndoMT. In addition, Ang II treatment in cultured MGECs induced EndoMT, decreased Foxo3A deacetylation and increased reactive oxygen species (ROS), while these effects were facilitated by SIRT3 overexpression. Upregulation of SIRT3 promoted endothelial function maybe through Foxo3A and ROS signaling pathway. Conclusions: This study indicates that SIRT3 mediated EndoMT is a novel pathway leading to fibrotic development in hypertensive renal fibrosis, suggesting that improvement of endothelial function by enhancing SIRT3 may be a new strategy to retard the progression of renal injury.